Graptolites and trilobites from the Eusebio Ayala Formation (Hirnantian?-early Llandovery), Paraná Basin, eastern Paraguay - Alfaro, Marta Beatríz (2012)
A low-diversity graptolite fauna fromthe upper part of the Eusebio Ayala Formation exposed in the intracratonic Paraná Basin of eastern Paraguay is reported herein. The sections studied are composed dominantly of red micaceous mudstones with intercalations of purple sandstones from a series of clay quarries (Santa Elena; Galeano; Western Itauguá) around Itauguá city. The graptolites Metaclimacograptus sp., Normalograptus cf. ajjeri (Legrand), and Normalograptus cf. medius (Törnquist) indicate an early Llandovery age for the upper Eusebio Ayala unit. Compared to coeval, postglacial successions in southwestern Gondwana, the graptolites studied have their closest affinities with those from the Rhuddanian lower Lipeón (Subandean Ranges, northwestern Argentina) and La Chilca (Precordillera) formations. In addition, a trilobite assemblage dominated by the genus Mucronaspis was collected from the Eusebio Ayala Formation type locality near Eusebio Ayala city. The latter represents an isolated small outcrop which seems to be latest Ordovician (Hirnantian) in age.